Koherensi Kausalitas Teks Berita Kompas - Suci Ayu Latifah (Universitas Suryakancana, 2025)
Coherence is the unity between sentences so as to produce a unity of meaning. Meaning is something that matters. For this reason, in news text discourse, causes and effects, or causality, are pursued. Causal coherence tries to find the causes and effects of a problem topic reported in the print media. The aim of this research is to describe markers of causality consistency in the Kompas media news text, October 2021 edition. The method used in the research is qualitative descriptive, with data analysis techniques. The findings of this research show that there is causal coherence or cause-and-effect coherence between sentences in every news article. The application of causal coherence is often found in the opening paragraph.Keywords: news; causality; coherence; text; discourseABSTRAKKoherensi merupakan kepaduan antarkalimat sehingga menghasilkan kesatuan makna. Makna adalah sesuatu yang berarti. Untuk itu, pada wacana teks berita dikejar sebab-akibatnya, atau kausalitasnya. Koherensi kausalitas berusaha menemukan sebab-akibat dari sebuah topik permasalahan yang dikabarkan di media-media cetak. Adapun tujuan penelitian ini mendeskripsikan penanda kekohensian kausalitas teks berita media Kompas edisi Oktober 2021. Metode yang digunakan dalam penelitian berupa deksriptif kualitatif, dengan teknik analisis data. Hasil temuan penelitian ini menunjukkan adanya penulisan koherensi kausalitas atau koherensi sebab-akibat antarkalimat di setiap tulisan pemberitaan. Pengaplikasian koherensi kausalitas tersebut banyak dijumpai pada paragraf pembuka.Kata Kunci: berita; koherensi; kausalitas; teks; wacana